Vertical distributions of soil carbon and nitrogen fractions as affected by land-uses in the Ili River Valley. Issue 2 (7th February 2017) - Liu, Xiang; Liu, Xuegong; Mu, Shuyong; Ma, Zhiwen; Li, Qian; Li, Lanhai
ABSTRACT: In this study, soil samples were collected to a depth of 100 cm from different land-uses, including maize field (MZ), wheat field (WT), paddy field (PD), apple orchard (OC), grassland (GL) and wetland (WL) in the Ili River Valley in northwest China, to investigate the effects of land-use on vertical distributions of soil carbon (C) and nitrogen (N) fractions, and examine whether such effects were different between topsoil (0–40 cm) and subsoil (40–100 cm). The results showed that soil organic C, water-extractable organic C, microbial biomass C, total N and microbial biomass N of croplands (MZ, WT, PD and OC) were significantly lower than those of natural lands (GL and WL) in both topsoil and subsoil, indicating that contents of soil C and N fractions can be reduced by agricultural land-uses, and the reductions are not limited to topsoil. However, the contents of soil ammonium N and nitrate N showed complex trends under different land-uses, possibly due to that the plant species and agricultural practices (e.g. application rate of fertiliser and irrigation) are considerably different among land-uses. Therefore, we suggest that more nutrient inputs should be applied to croplands to improve soil fertility in the Ili River Valley.